PROFILE PEDAGOGICAL CONTENT KNOWLEDGE (PCK) OF PRIMARY SCHOOL TEACHER IN SCIENCE TEACHING - Yuliariatiningsih, Margaretha Sri; Halimah, Lely; Yanthi, Novi; Wahyuningsih, Yona (Universitas Pendidikan Indonesia, 2019)
This research is to know pedagogical content knowledge (PCK) of primary schools teacher in science lesson. The research method used survey method. Research subject is determined by purposive sampling technique. Research data were collected by interview technique, questionnaire, test, product assessment, and observation. Data were analyzed by one-way Anova toward civil servant period, certification period, work class, GPA and university origin. The conclusions obtained indicate that the teacher's PCK in teaching science in primary schools depends on the newly-conducted training program such as the Teacher Education and Professional Training (PLPG). There is no correlation between the underlying factors as a teacher and the PCK in significantly teaching science in primary schools. It is recommended that teachers regularly attend training related to the updating of learning materials or related to PCK as the basis of the teaching profession in teaching science through an in service training program.